Civic Technology for Social Innovation - Saldivar, Jorge; Parra, Cristhian; Alcaraz, Marcelo; Arteta, Rebeca; Cernuzzi, Luca (Computer Supported Cooperative Work (CSCW), 2019)
The recent surge of investment in Civic Technologies represents a unique opportunity to realize the potential of Information and Communication Technologies (ICTs) for improving democratic participation. In this review, we study what technologies are proposed and evaluated in the academic literature for such goal. We focus our exploration on how civic technology is used in the collaborative creation of solutions for social issues and innovations for public services (i.e., social innovation). Our goal is to provide researchers, designers, and practitioners a starting point to understand both the academic state of the art and the existing opportunities for ICT in a democracy.
Number: 1
Keywords: Computer Supported Cooperative Work (CSCW); Réservé UdeM